Non-financial KPIs in annual report narratives: Australian practice. Issue 1 (7th May 2019) - Bayne, Lyndie; Wee, Marvin
Abstract : Purpose: The purpose of this paper is to provide preliminary evidence on current practices in non-financial key performance indicator (KPI) reporting in annual reports by listed Australian companies to inform Australian legislators and accounting standard setters contemplating regulations and guidance for non-financial performance disclosure, including input into the revision of IFRS Practice Statement 1: Management Commentary (2010). Design/methodology/approach: Non-financial KPIs were hand-collected from the annual report narratives of 40 listed Australian companies from five sectors in 2016. Trends in the type, quantity, comparability and range of non-financial KPIs were analysed, and the association between company characteristics and non-financial disclosure was explored. Findings: In total, 78 per cent of the sampled companies disclose non-financial KPIs in their annual reports, reporting 11 non-financial KPIs per company on average. The most common category is Employee, followed by Environment, accounting for 68 per cent of non-financial KPIs. Provision of comparators is low, with only 28 per cent of non-financial KPIs disclosed with prior year results and 24 per cent disclosed with a target. Companies disclose across a median of two out of seven categories. Company size is shown to be associated with non-financial measures. Originality/value: The study contributes initial detailed empirical Australian evidence of non-financial KPI reporting practices. A framework is established for assessing non-financial KPI disclosure, adding to voluntary disclosure studies. A data collection method is developed for collecting KPIs from annual report narratives, contributing to the methodology used in voluntary reporting content analysis.